Reconceptualizing Stage-Based Legal Proceedings: A Comparative Analysis of European Models and Judicial Reform in Ukraine - Ihor Bychkov; Yevhen Romanchenko; Anatolii Petrenko; Ivan Kaylo; Andrii Svintsytskyi (Universitas Muhammadiyah Bandung, 2026)
This paper examines the stage-based approach to the organization of legal proceedings in the justice systems of Europe and Ukraine. Staging is understood as a procedural framework that structures judicial activity into successive phases, ensuring fairness, transparency, and efficiency of the trial process. The study analyses key stages of legal proceedings, including pre-trial investigation, preparatory procedures, trial, and appellate review, highlighting their role in protecting procedural rights and upholding the rule of law. Using a comparative legal approach, the research explores the practices of Germany, the United Kingdom, France, Italy, and Spain to identify common features and differences in stage-based models. Particular attention is given to the influence of European legal standards and international judicial practice on national systems, as well as to the challenges of adapting these approaches in Ukraine. The paper identifies major shortcomings in the Ukrainian judicial process, such as inefficiencies in pre-trial investigation and limited effectiveness of judicial control. The findings show that a well-structured stage-based system enhances legal certainty and the protection of human rights. The study concludes that Ukraine should develop a functionally effective procedural model based on European best practices while considering national legal realities.